PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN QUALITY PRODUCT TRAINING DALAM MENINGKATKAN KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Adyarta, Kartika Dewi (JURNAL BISNIS STRATEGI, 2016)
This study aimed to analyze the effect of Transformational Leadership, Training of Product Quality, and Motivation on Employee Performance. The selected research object in this study are employees of BCA KCU Gang Tengah, Semarang.Data were collected through questionnaires filled out independently by 120 respondents selected by random sampling method Proportionate Startified. Measurement of exogenous and endogenous constructs were tested using confirmatory factor analysis, and the results showed that the full feasibility test models are in the range of expected values.The results of this study prove and the conclusions that: (1) Transformational leadership has significant effect on the motivation, (2) Training of Product Quality has significant impact on the motivation, (3) Transformational Leadership significant effect on the performance of employees, (4 ) Training of Product Quality has significant impact on the performance of employees, (5) Motivation has significant impact on the performance of employees, (6) transformationalleadership has significant impact on the performance of employees through employee motivation, and (7) Training of Product Quality has significant impact on employee performance through motivation.Â